Assessment of a consultation-liaison psychiatry and psychology health care program - Andreoli Paola BA; Mari Jair de J (Universidade de São Paulo, 2002)
OBJECTIVE: To investigate the relevance of subjective criteria adopted by a psychiatry and psychology consultation-liaison service, and their suitability in the evaluation of case registries and objective results. METHODS: Semi-structured interviews were conducted and all supervisors of the university hospital service were interviewed. Routinely collected case registries were also reviewed. Standardized assessment with content analysis for each category was carried out. RESULTS: The results showed distortions in the adopted service focus (doctor-patient relationship) and consultant requests. This focus is more on consulting physician-oriented interventions than on patients. DISCUSSION: Evaluation of the relevance of service criteria could help promoting quality assessment of the services provided, mainly when objective criteria have not yet been established to assure their suitability.